Caracterização ambiental da bacia do Alto Jacaré-Guaçu (experimentos laboratoriais e in situ): elaboração de sedimentos sintéticos para avaliação da toxicidade do cádmio - Rodrigues, Beatriz Kawamura (Universidade Federal de São Carlos, 2011)
The Alto Jacaré-Guaçu Basin was evaluated regarding limnological and ecotoxicological aspects in four water and sediment sampling campaigns at 14 points distributed in the area. Toxicity tests with water, in the laboratory and in situ, showed chronic toxicity, with effects on the survival, growth and gill morphology of juveniles of both fish species examined (Danio rerio and Poecilia reticulata). The lowest survival percentages in the laboratory assays were observed for point L, and in the field tests for point J1. The analysis of the gills revealed first-stage alterations in the specimens of both species exposed at all the sample points, and there were second-stage alterations (aneurism and vascular congestion) at various points. The high concentrations of nutrients and metals in the basin s water and sediments reveal a system impacted by human activities in the surrounding region. The analyses of metals quantified Cd, Cr, Cu, Mn and Fe levels in the water above those permitted by the Brazilian National Environmental Council (CONAMA 357/05), and of Cd in the sediments above the threshold levels permitted both by national (CONAMA 344/04) and international regulations (CCME, 2003). Simple synthetic sediments were prepared composed of sand, clay and organic matter (obtained from the aquatic macrophyte Scirpus cubensis, at concentrations of 0, 0.25, 0.5 and 1%) to assess the toxicity of Cd. The synthetic sediments were viable for the growth and survival of Ceriodaphnia silvestrii, Chironomus xanthus and Danio rerio, and were suitable for use in spiked experiments. The evaluation of the acute toxicity of the sediments fortified with Cd indicated mean 48-h;EC50 for C. silvestrii of 3.09mg.Kg-1 in the sediments with 0% OM and 2.98mg.Kg-1 in the sediments with 1% OM. The mean 96-h;LC50 for C. xanthus was 18.67 mg.Kg-1 in the sediments with 0% OM and nearly four times lower in those with 1% OM (4.93 mg.Kg-1). A similar pattern was noted for D. rerio, a higher 48-h;LC50 in the sediments with 0% OM (114.88 mg.Kg-1) than in the sediments with 1% OM (75.31 mg.Kg-1). In subsequent experiments, the sediments were also spiked with 0.6mg.Kg-1 of Cd, a concentration considered safe for protection of aquatic life according to the applicable national and international regulations. In these tests, the survival of C. silvestrii was impaired in the Cd spiked sediments, so it was not possible to assess the effects on reproduction. There were also effects on the survival, biomass, mentum morphology and Cd concentration in the tissues of C. xanthus. For D. rerio, the survival and growth were compromised in the sediments with higher percentage of organic matter. Besides this, the organisms showed impaired gill morphology and higher Cd concentration in tissue in function of exposure to sediments spiked with the metal. Based on the results, it can be concluded that C. silvestrii was the most sensitive species to the sediments fortified with Cd, followed by C. xanthus and D. rerio, the least sensitive. These effects on the iv organisms at concentrations considered safe for the biota suggest more conservative thresholds of this metal should be established for tropical aquatic habitats.
Environmental characterization of the Alto Jacaré-Guaçu River Basin (Laboratory and In situ experiments): Formulation of synthetic sediments for assessing the toxicity of cadmium
Keywords: Limnologia; Ecotoxicologia; Toxicidade - testes; Cadmio; Danio rerio; Ceriodaphnia silvestrii; Chironomus xanthus; Danio rerio; Poecilia reticulata; In situ toxicity tests; Cadmium toxicity; CIENCIAS BIOLOGICAS::ECOLOGIA